DAMPAK KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM MENUMBUHKAN KEDISIPLINAN SISWA KELAS XI DI SMK NEGERI 11 BANDUNG - Supriyatno Supriyatno; Ansori Ansori; Dinno Mulyono (Comm-Edu (Community Education Journal), 2023)
This study aims, firstly, to determine the process of implementing extracurricular activities in fostering student discipline at SMK Negeri 11 Bandung. The theory used in this study is the theory (Soegeng PP., 1995:23) in Tu'u (2004: 31), the theory of the 1995 National Discipline Crash Working Group Team (GDN 1996:29-30) in Tu'u (2004: 32), and theory (Maman R. 1999:168) in Tu'u (2004: 32). This study uses a qualitative descriptive approach, with the research subject 5 students of class XI SMKN 11 Bandung. The instruments used are observation, interviews, and documentation. Data analysis uses technical analysis (data reduction, data display, and conclusion drawing). The results showed that there was a change in the level of discipline of students who took part in scout extracurricular activities. This is based on the results of homeroom interviews, student observations and a study of student record documentation on BK teachers at SMKN 11 Bandung. The conclusion of this study shows that the scout extracurricular has an impact on the level of student discipline. Keywords: Discipline, Scout Extracurricular.